Optimization of electron beam parameters of LIA-10M accelerator - Gordeev, V.S.; Mikhailov, Е.S.; Myskov, G.A.; Viktorov, I.V.; Parshina, I.V. (Вопросы атомной науки и техники, 2006)
A numerical simulation of the LIA-10M accelerator was carried out. It is shown that at the existing configuration
of the diode unit and maximal for LIA-10M injection parameters (3 MeV, 50 kA) significant (up to 40%) beam losses
in the accelerating channel are possible. As a result of calculations the injector cathode geometry was optimized
what permitted to avoid beam electron leakage onto the walls of accelerating channel and to improve significantly
output parameters of the LIA-10M accelerator. Проведено численное моделирование ускорителя ЛИУ-10М. Показано, что при существующей конфигурации диодного узла и максимальных для ЛИУ-10М параметрах инжекции (3 МэВ, 50 кА) возможны значительные (до 40%) потери пучка в ускорительном тракте. В результате расчетов оптимизирована геометрия катода инжектора, что позволило избежать утечки электронов пучка на стенки ускорительного тракта и существенно улучшить выходные параметры ускорителя. Проведено чисельне моделювання прискорювача ЛІП-10М. Показано, що при існуючій конфігурації діодного вузла і максимальних для ЛІП-10М параметрах інжекції (3 МеВ, 50 кА) можливі значyі (до 40%) втрати пучка в прискорюючому тракті. У результаті розрахунків оптимізована геометрія катода інжектора, що дозволило уникнути витоку електронів пучка на стінки прискорюючого тракту і суттєво поліпшити вихідні параметри прискорювача.